Cryptocurrency reaction to FOMC Announcements: Evidence of heterogeneity based on blockchain stack position - Corbet, Shaen; Larkin, Charles; Lucey, Brian; Meegan, Andrew; Yarovaya, Larisa (Journal of Financial Stability, 2020)
We examine the response of a broad set of digital assets to US Federal Fund interest rate and quantitative easing announcements, specifically examining associated volatility spillover and feedback effects. We classify each digital asset into one of three categories: Currencies; Protocols; and Decentralised Applications (dApps). Currency-based digital assets experience idiosyncratic spillovers in the period immediately after US monetary policy announcements, while application or protocol-based digital assets are largely immune to policy volatility spillover and feedback. Mineable digital assets are found to be more susceptible to monetary policy volatility spillovers and feedback than non-mineable. Responses indicate a diverse market within which, not all assets are comparable to Bitcoin.